The Effect of Binder Concentration on the Ability of Gelcasting Porous Ceramics as TiO2 Support Catalysts - Suriati Eka Putri; Diana Eka Pratiwi; Rachmat Triandi Tjahjanto; Abd. Rahman (Indonesian Journal of Fundamental Sciences, 2022)
Abstract. This study aims to determine the effect of binder concentration on the ability of porous ceramics as TiO2 support catalyst. The porous ceramic synthesis used was the gelcasting method using natural clay as matrix, cassava starch as binder and CMC as dispersant. The concentration of cassava starch binder used were 2%, 4%, 6%, 8%, 10%. The methods used in catalyst supporting are adsorption method and sol gel coating method. Analysis of TiO2 catalyst content in porous ceramics using XRF instrument. The results obtained showed that the concentration of cassava starch affects the ability of porous ceramics as TiO2 catalyst support. The largest percentage of TiO2 catalyst with adsorption method was achieved at a binder concentration of 8% with a catalyst percentage of 38.9% while with sol gel coating method was achieved at a binder concentration of 4% with a catalyst percentage of 20.11%. Keywords: Binder, Cassava Starch, Porous Ceramic, Gelcasting, Support Catalysts